Fitting new constructal models for the thermal potential of earth-air heat exchangers - Ramalho, Jairo Valões de Alencar; Brum, Ruth da Silva; Rocha, Luiz Alberto Oliveira; Isoldi, Liércio André; Santos, Elizaldo Domingues dos; Sulzbacher, Mariane (Acta Scientiarum. Technology, 2018)
Â Relying on the Constructal Design method, this paper introduces new periodic models for the thermal potential of Earth-Air Heat Exchangers (Eahe). As a case study, it analyses the best spacing for three ducts arranged triangularly in order to maximize the heat transfer between soil and air. More specifically, the ratio Â between the horizontal and vertical spaces among the ducts is set free to vary up to limiting global constraints. This paper aims to better understand how the variations in Â affect the thermal performance of Eahe. As an additional contribution, some relationships between Â and the thermal potential of Eahe are mathematically and continuously stated. This allows establishing additional results for the efficiency and energetic performance of Eahe, as well as recommend arrangements in the shape of isosceles triangles with base and height unitary. Â